Automated planter for children's education on plant care - Condori-Tito, Jesus; Flores-Rodriguez, Nino; Huaracha-Carlos, David; Lonasco-Santamarina, Leonardo; Nuñez-Arista, Piero; Esquicha-Larico, Elias; Mamani-Machaca, Elizabeth (LACCEI, 2024)
This study focused on evaluating the effectiveness of an automated planter as an educational tool to teach children about environmental and plant care. A quantitative research methodology was used to collect data on the perception and impact of the device. The results show that the interactive planter, equipped with humidity, light, and pH sensors, was effective in engaging children in the direct care of a plant. This helped bridge the gap between theoretical knowledge and practical action, fostering sustainable habits and greater environmental awareness in the participants. Quantitative data revealed positive patterns and trends regarding the pot's effectiveness in educating children at 97.2%. Overall, the study findings suggest that the implementation of interactive technologies such as the automated planter may be a promising solution to address the challenges of environmental education in children. By combining technology with nature, these types of educational tools can help cultivate sustainable habits and an emotional connection to the environment from an early age.